How does workplace support promote postdoctoral career growth? A conservation of resources perspective - Li, Xueyan; Hu, Anqi; Song, Hongfeng; Wang, Zhimei (Frontiers in Psychology, 2024)
Postdoctoral researchers are critical to scholarly advancements, and promoting postdoctoral career growth is an endogenous path to help postdocs break through the “encircled city of scientific research”. However, further research is needed to fully explore the mechanisms that connect workplace support to postdoctoral career growth. Drawing from the Conservation of Resources theory, this study proposes a chain mediation model that demonstrates how workplace support enhances career growth by connecting psychological capital with work-life balance. Analyzing 367 questionnaires from Chinese postdocs, our research indicates that workplace support can have a positive impact on career growth. Additionally, both psychological capital and work-life balance are key factors that contribute to career growth, serving as separate mediators and as part of a chain of mediators. This study validates the appropriateness of the Conservation of Resources theory in the study of the influence mechanism of postdoctoral career growth and proposes targeted strategies for academic institutions to improve support systems, promoting more effective career development pathways.